IMPROVING DIAGNOSIS OF THE PROLONGED JAUNDICE IN FULL-TERM BREAST- FED INFANTS - Yesipova, S.I. (World of Medicine and Biology, 2019)
The article presents clinical and anamnestic characteristics and features of the pro- and anti-inflammatory cytokines balance in infants with prolonged jaundice (PJ) at breastfeeding. Factors of prolonged jaundice in newborns on the part of mothers (risk of abortion, somatic pathology, impaired lactation) and infants (morphofunctional immaturity of the newborn, diseases during the neonatality) were identified. Distribution of infants in groups was based primarily on the of total bilirubin indices, and secondly, jaundice was divided into jaundice due to breastfeeding and jaundice from mother’s milk. Pro-inflammatory cytokines indices growth and epidermal growth factor (EGF) in all infants with prolonged jaundice were determined. A correlation between IL-1β, EGF and total bilirubin in blood serum of infants with breast milk PJ was established. The prolonged course of jaundice from breast milk can be explained by the increased content of EGF in blood serum. In infants with PJ due to breastfeeding, inadequate lactation is accompanied by the increased hepatic circulation and the increased serum bilirubin concentration.